UPAYA PENERTIBAN LALU LINTAS MELALUI SISTEM ELECTRONIC TRAFFIC LAW ENFORCEMENT DENGAN PENGAWASAN CCTV DI KOTA SURABAYA PUSAT - Ayoma Sakti, Harlu Aza (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2023)
Many road users are disorderly, resulting in many traffic violations until due to road accidents, the government has tried to develop technology in traffic safety and road transportation by implementing the E-TLE system through CCTV traffic surveillance cameras, which are installed at certain points of the road, the purpose of this study is to determine the constraints of the electronic ticketing system (E-TLE) using CCTV surveillance cameras Traffic in trying to control motorists, including the obstacles faced by officers in implementing an electronic ticketing system (E-TLE), this study is an empirical research with a socio-legal approach on the implementation of the E-TLE system through CCTV Traffic Surveillance in an effort to regulate road users in Central Surabaya City and discusses the problem of how obstacles faced by the police in implementing the e-TLE system through CCTV traffic monitoring in an effort regulate road users in the city of Surabaya The results of research on the obstacles felt by the police in implementing E-TLE, including smooth supervision from minimal officers and minor abuse